(untitled) (Tabanque. Revista Pedagógica, 2018)
During this article, we will enter into the reflexive capacity of art, specifically urban art, serving as a catalyst for social and community processes. In addition, we will establish points of union with the work of the Social Educator and the artivism or activism from the art and how all this can help the feminist claim. To do this, we will briefly delve into the work of different women urban artists, natives of different countries and thus establish a map that covers different latitudes and ways of intervening in the urban space. Finally, we will comment briefly one intervention, carried out in an adult classroom and thus demonstrate the previously discussed possibilities of urban art for social intervention.